Socio-demographic Characteristics of Depressive Illness Patients Attending a Selected Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Depressive illness is generally not perceived as an important public health problem and is not priority in health care delivery system in Bangladesh. It is the leading cause of disease-related disability in the country today. Gender differences in depression are likely to be result of certain risk factors.Objectives: To find out gender difference in epidemiological and socio-demographic features associated with depressive illness.Materials and Methods: This descriptive cross sectional study was carried out among 91 diagnosed depressive patients attending in the psychiatry department of CMH Dhaka from January to December 2014. The patients were interviewed through an interviewer-administered questionnaire. Data were analyzed by using SPSS version 20.  Chi-square test was used to see the level of significance.Results: In this study the mean age of the patients was 34.47±9.577 years. The study revealed that depressive illness appears to be  more in female during child bearing and child rearing period of 16-39 years and male of 40-63 years were more sufferer than female which was significantly different (p